Malignancy Risk Index 4 (RMI 4) is better than RMI 3 as a predictor Advanced Epithelial Ovarian Carcinoma was used for NACT - Putu Arik Herliawati; Dhian Eka Putri Harnandari; Rezha Alivia Hildayanti; Arghya Wicaksana; Pande Putu Firsta (Universitas Pahlawan Tuanku Tambusai, 2023)
Of the 4 cancers in women, ovarian carcinoma is the first cause of death. The low survival rate in patients with advanced stages requires early detection to improve treatment outcomes. The methods currently used to determine whether a patient can be given neoadjuvant chemotherapy are ascites cytology and laparoscopy.This study aims To compare RMI 4 and RMI 3 as a non-invasive method in determining preoperative NACT administration. The method used is RMI 3 and RMI 4 diagnostic scoring where this method can be used as a predictor of advanced epithelial ovarian carcinoma in the interest of NACT. An analytical observational study with a retrospective cross sectional type study with samples of all patients suffering from ovarian cancer for the past 5 years, from January 2016 to January 2020 who had been diagnosed at the Gynecology Polyclinic RSUD dr. Saiful Anwar. The number of initial samples of this study was 253 women, but after being included in the inclusion criteria, there were 106 samples. After staging by an authorized clinician, there were 48 patients with early stage and 58 patients with advanced stage. Between the results of the RMI score and the histopathological results on the ROC curve, it was found that the accuracy value of RMI 3 is 84.9% and the accuracy value of RMI 4 is 86.8%. It can be concluded that RMI 4 is better than RMI 3 as a predictor of advanced ovarian carcinoma to determining preoperative NACT administration.